KONSEP KEBEBASAN DALAM PENDIDIKAN PERSPEKTIF RABINDRANATH TAGORE DAN RELEVANSINYA BAGI PENGEMBANGAN SISTEM PENDIDIKAN DI INDONESIA - Gede Agus Siswadi (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Education is simply a tool to liberate humans from ignorance. However, this becomes a paradox between being a liberating tool and actually being a tool that shackles humans. Various existing systems in education are now manifesting as tools that impede human freedom to be able to learn happily. Educational observers have initiated the concept of critical education including Paulo Freire, Ivan Illich, John Holt, Reimer, Henry Giroux and one of them discussed in this article is Rabindranath Tagore. This study uses a qualitative method with a philosophical hermeneutic approach. The data in this study were collected through library research. The results in this study explain that Rabindranath Tagore based his criticism of education in India during the British colonial period which tended to focus on materialistic and intellectualistic aspects and did not pay attention to spiritual, emotional, social, and also nationalism aspects. Education that Rabindranath Tagore feels is more likely to only give birth to students who are uniform and do not pay attention to the potential or interests and talents of students naturally. The idea offered by Rabindranath Tagore is education that liberates with elements of art in education. Rabindaranath Tagore's thoughts can be used as an idea to design an education system in Indonesia, especially a humanist education system.